Occupational accidents with exposure to biological material in nursing and medical professionals in Brazil (Research, Society and Development, 2022)
Objective: to describe the occurrence profile of occupational accidents with exposure to biological material among nursing and medical professionals in Brazil. Methodology: ecological temporal trend study, carried out with data on occupational accidents in nursing and medical professionals with exposure to biological material obtained from the Department of Informatics of the Unified Health System (DATASUS), from 2012 to 2022. Results: observed- a higher prevalence of occupational accidents with biological material among women, young professionals, with technical level training, involving manipulation of sharp objects, during medication administration, puncture and surgical procedures. Conclusion: the results highlight the importance of reporting cases and implementing effective programs on the prevention and control of work-related accidents with biological material.